1997
DOI: 10.1002/chin.199720003
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: X‐Ray Diffraction Study of Yttrium Iodide.

Abstract: structure structure (solids and liquids) D 2000 -003X-Ray Diffraction Study of Yttrium Iodide.-YI3, obtained by direct iodination of the metal, crystallizes in the hexagonal system (Z=18). It proves to be isostructural to LuI3, HoI3, and GdI3 and belongs to the structure type BiI3. -(ASTAKHOVA, I. S.; GORYUSHKIN, V. F.; EPIFANTSEV, O. G.; Zh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This implicates that the bulk structure does not contain a perfectly ordered set of identical layers. Parenthetically, it is worth mentioning that in a previous study 43 the crystal structure was also reported using a hexagonal cell (space group 143), thus pointing out the same conclusion. In order to check if such disorder could have any noticeable influence in our calculations, we performed structural optimizations using either a small perfectly ordered rhombohedral cell or a larger hexagonal cell with more structural freedom.…”
Section: D Lui 3 : From Monolayer To Bulksupporting
confidence: 64%
“…This implicates that the bulk structure does not contain a perfectly ordered set of identical layers. Parenthetically, it is worth mentioning that in a previous study 43 the crystal structure was also reported using a hexagonal cell (space group 143), thus pointing out the same conclusion. In order to check if such disorder could have any noticeable influence in our calculations, we performed structural optimizations using either a small perfectly ordered rhombohedral cell or a larger hexagonal cell with more structural freedom.…”
Section: D Lui 3 : From Monolayer To Bulksupporting
confidence: 64%